Plant cell wall imaging by metabolic click‐mediated labelling of rhamnogalacturonan II using azido 3‐deoxy‐d‐manno‐oct‐2‐ulosonic acid. (30th January 2016) - Dumont, Marie; Lehner, Arnaud; Vauzeilles, Boris; Malassis, Julien; Marchant, Alan; Smyth, Kevin; Linclau, Bruno; Baron, Aurélie; Mas Pons, Jordi; Anderson, Charles T.; Schapman, Damien; Galas, Ludovic; et al.
Summary: In plants, 3‐deoxy‐d ‐ manno ‐oct‐2‐ulosonic acid (Kdo) is a monosaccharide that is only found in the cell wall pectin, rhamnogalacturonan‐II (RG‐II). Incubation of 4‐day‐old light‐grown Arabidopsis seedlings or tobacco BY‐2 cells with 8‐azido 8‐deoxy Kdo (Kdo‐N3 ) followed by coupling to an alkyne‐containing fluorescent probe resulted in the specific in muro labelling of RG‐II through a copper‐catalysed azide–alkyne cycloaddition reaction. CMP‐Kdo synthetase inhibition and competition assays showing that Kdo and D‐Ara, a precursor of Kdo, but not L‐Ara, inhibit incorporation of Kdo‐N3 demonstrated that incorporation of Kdo‐N3 occurs in RG‐II through the endogenous biosynthetic machinery of the cell. Co‐localisation of Kdo‐N3 labelling with the cellulose‐binding dye calcofluor white demonstrated that RG‐II exists throughout the primary cell wall. Additionally, after incubating plants with Kdo‐N3 and an alkynated derivative of L‐fucose that incorporates into rhamnogalacturonan I, co‐localised fluorescence was observed in the cell wall in the elongation zone of the root. Finally, pulse labelling experiments demonstrated that metabolic click‐mediated labelling with Kdo‐N3 provides an efficient method to study the synthesis and redistribution of RG‐II during root growth. Significance Statement: Rhamnogalacturonan II (RG‐II) is a component of pectin that is important for primary cell wall synthesis and elongation, but little is known about its biosynthesis or its in planta localisation and turnover. Here we show that metabolic click‐mediated labelling can be used to monitor deposition and remodeling of pectins within the apoplast.